2017
DOI: 10.1038/s41598-017-17140-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of watermelon (Citrullus lanatus) fruits in response to Cucumber green mottle mosaic virus (CGMMV) infection

Abstract: Cucumber green mottle mosaic virus (CGMMV) belongs to the Tobamovirus genus and is a major global plant virus on cucurbit plants. It causes severe disease symptoms on infected watermelon plants (Citrullus lanatus), particularly inducing fruit decay. However, little is known about the molecular mechanism of CGMMV-induced watermelon fruit decay. For this study, comparative analysis of transcriptome profiles of CGMMV-inoculated and mock-inoculated watermelon fruits were conducted via RNA-Seq. A total of 1,621 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 57 publications
2
62
0
Order By: Relevance
“…However, there are still no reports on proteomic profiles in response to CGMMV infection in watermelon, especially in fruits. In a previous study, we utilized HTS technology to analyze the transcriptomic changes of CGMMV-inoculated watermelon fruits [30]. In this study, we further employed the iTRAQ technique to carry out a comparative study of the proteomic profiles between CGMMV-inoculated and mock-inoculated watermelon fruits to explore the molecular mechanisms underlying "watermelon blood flesh" caused by CGMMV infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there are still no reports on proteomic profiles in response to CGMMV infection in watermelon, especially in fruits. In a previous study, we utilized HTS technology to analyze the transcriptomic changes of CGMMV-inoculated watermelon fruits [30]. In this study, we further employed the iTRAQ technique to carry out a comparative study of the proteomic profiles between CGMMV-inoculated and mock-inoculated watermelon fruits to explore the molecular mechanisms underlying "watermelon blood flesh" caused by CGMMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the expression levels of CS and UGE were induced, while PK and HK3 were significantly downregulated after CGMMV infection. Significant changes in sugar contents (sucrose, glucose, and fructose) of watermelon fruits were found after CGMMV infection [47], and the genes related to pyruvate metabolism and the fermentation pathway were also strongly affected by CGMMV infection at the transcriptional level [30]. Therefore, it is speculated that CGMMV infection may influence the pyruvate metabolism and citrate cycle, and further cause a disturbance in the energy supply and sugar content in the watermelon fruits.…”
Section: Changes In Carbohydrate Metabolism After Cgmmv Infectionmentioning
confidence: 99%
See 3 more Smart Citations